ETIKA PEMERINTAH DALAM MEWUJUDKAN BIROKRASI YANG BAIK (GOOD GAVERNANCE) (Studi Kasus Di OPD Kecamatan Jatirejo Kabupaten Mojokerto): Studi Kasus Di OPD Kecamatan Jatirejo Kabupaten Mojokerto - Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Majapahit Mojokerto, Mohammad Robibin Abdul ; Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Majapahit Mojokerto, Ahmad Hasan Afandi; Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Majapahit Mojokerto, Hikmah Muhaimin (Government Studies Departement of Universitas Islam Majapahit, Indonesia, 2021)
ABSTRACT : In providing services to the public, the government is expected to be able to carry out its duties and authorities properly and not abuse its position and is expected to uphold the values ??and norms that exist in the community, which is commonly referred to as ethics. Discipline of the apparatus/employees is a benchmark in the realization of a good bureaucracy (Good Gavernance), because the main function of the apparatus/employees is to serve the public and is also more concerned with the public interest than their own interests. With the ethics and code of ethics for Civil Servants, it can make the apparatus/employees more efficient and responsible for the duties and authorities given to them, the government administration process will also be able to run smoothly if the behavior of the apparatus follows ethical values.Based on the results of research that has been obtained through several informants that government ethics can be seen in the implementation of the code of ethics for Civil Servants (PNS) with program efforts that can create good conditions. The results of the study prove that the quality and quantity of human resources of the apparatus/employees is still low and is also hampered by several other factors. With the programs that are run, it is expected to provide an increase in the quality of human resources in the future so that the services provided will be able to run well and the community can feel satisfied with the services provided.